2020
DOI: 10.1002/solr.202000320
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible and Transparent Polylactic Acid Composite Electrode for Perovskite Solar Cells

Abstract: Biomass substrates are urgently needed to develop green electronics. Herein, an ultra‐flexible and transparent biomass‐derived conductive substrate is originated from nature polylactic acid (PLA) with silver nanowires (AgNWs) modified by PH1000. The composite electrode exhibits low sheet resistance of 25 Ω sq−1, high transmittance (over 82% in the region of 400–800 nm), and excellent mechanical durability. After bending tests of 15 000 times at a curvature radius of 3 and 5 mm, the sheet resistances of the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…The development of transparent electrodes contributes to the realization of semitransparent f-PSCs, which are promising to work in smart displays and windows. Jang et al reported semitransparent f-PSCs with both transparent electrodes fabricated by graphene doping with bis­(trifluoromethanesulfonyl)­amide (TFSA) and triethylenetetramine (TETA), which realized PCEs of 10.56 and 10.73% at two sides, respectively . The research on all-inorganic f-PSCs is conducive to solving the stability problem owing to their good thermal and illumination stabilities. Lead-free f-PSCs can reduce the heavy metal pollution of lead. An adjustable band gap makes f-PSCs applicable in tandem solar cells. Additionally, a series of low-cost, environmentally friendly, and biocompatible materials have been employed in f-PSCs. Undoubtedly, these investigations will facilitate the commercial applications of f-PSCs.…”
Section: Applications Of F-pscsmentioning
confidence: 99%
“…The development of transparent electrodes contributes to the realization of semitransparent f-PSCs, which are promising to work in smart displays and windows. Jang et al reported semitransparent f-PSCs with both transparent electrodes fabricated by graphene doping with bis­(trifluoromethanesulfonyl)­amide (TFSA) and triethylenetetramine (TETA), which realized PCEs of 10.56 and 10.73% at two sides, respectively . The research on all-inorganic f-PSCs is conducive to solving the stability problem owing to their good thermal and illumination stabilities. Lead-free f-PSCs can reduce the heavy metal pollution of lead. An adjustable band gap makes f-PSCs applicable in tandem solar cells. Additionally, a series of low-cost, environmentally friendly, and biocompatible materials have been employed in f-PSCs. Undoubtedly, these investigations will facilitate the commercial applications of f-PSCs.…”
Section: Applications Of F-pscsmentioning
confidence: 99%
“…Fallahi et al obtained a conductive, flexible, and transparent film based on PLA and silver nanowires (AgNWs) which could be used as substrate for optoelectronic devices 29 . Recently, OLEDs 30 and perovskite solar cells 31 were fabricated on top of AgNWs/PLLA:PDLA and AgNWs/PH1000 (highly conductive poly(3,4‐ethylenedioxythiophene):poly‐(styrene‐sulfonic acid) (PEDOT:PSS)/PLA films, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…9,[28][29][30][31][32] What's more, the vacuum deposition processing of TCOs also suffers from the high processing temperature (usually over 200 1C), low throughput and scarcity of indium, which is incompatible with the high throughput solutionprocessing and printing technologies. 25,[33][34][35][36] To address the abovementioned drawbacks, a variety of novel materials, such as metallic micro-nano architectures (MMNAs), [37][38][39][40][41][42][43][44][45][46][47] conducting polymers, [48][49][50][51][52][53] low-dimensional carbons, [54][55][56][57][58] and the composites formed by these materials, 49,[59][60][61][62][63][64] have been developed as promising candidates for flexible TEs. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows the sheet resistance and optical transmittance of different conductive materials recently reported. 10,40,41,52,56,61,[65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82] The FoM value is the factor to evaluate the performance of TEs, which can be calculated using eqn (1): 44,52 FoM ¼ 188:5O R s  TðlÞ À0: 5…”
Section: Introductionmentioning
confidence: 99%